Design method for glulam beams strengthened with flax fiber reinforced polymer sheets. (March 2023) - Di, Jing; Zuo, Hongliang; Li, Yishi; Wang, Zhaowen
Abstract: The strengthening efficiency of flax fiber reinforced polymer (FFRP) reinforcement is evaluated by four-point bending tests, conducted on full-scale glulam beams strengthened with FFRP sheets. Experimental variables include different layers (three-layer or six-layer), attaching types (unidirectional or bidirectional), and attaching configurations (longitudinal, U-shaped or fully wrapped). The failure modes, load-deflection curves, strain changes, load capacities, flexural rigidity, energy absorption, and ductility of the tested specimens were recorded and discussed. Results indicate that the bending performance of a beam strengthened with three-layer longitudinal FFRP sheets outperforms that of a six-layers. The strengthening efficiency of bidirectionally attached FFRP is significantly higher than that of unidirectionally attached FFRP. Furthermore, a theoretical model for the ultimate load of test beams was developed and validated on the basis of these results, demonstrating good agreement with the experimental results. The design value of tensile strength for FFRP sheets was determined by reliability analysis. Based on the test data and recommended values for tensile strength of FFRP sheets, the reliability indexes β for the design formulas were calculated to further verify their applicability and reliability. Finally, the global modification factors for design formulas were calculated and recorded to achieve the target reliability requirement ( β = 3.2 specified in the Chinese code GB50005-2017).